The Development of Mobile Japanese Halal Gamification (MJHG) - Mat, Ruzinoor Che; Kazunori, Miyata; Rahman, Azman Ab. (International Journal of Interactive Mobile Technologies (iJIM), 2020)
There are projected to be over 200,000 Muslim tourists will visit Japan due to expected Tokyo Olympics 2020. But the previous study showed that the level of understanding about Muslim needs such as Halal terms still low among Japanese people. There is a technique and approach such as gamification that need by the Japanese people to fulfill this requirement. Gamification which integrating game thinking and games element has been proven to help in learning new knowledge. That is why the objective of this study discusses how to develop an application of MJHG in a smartphone-based on the android system. The MJHG was design based on a well known visual novel concept that combining with multimedia elements included audio, animation, graphics, and image to make it more attractive and alive. All of these elements blending with the gamification elements such as quiz, rewards, badges, and feedback to make it as gamified applications. Based on all of these capabilities of MJHG, it, therefore, can help the potential users not only Japanese people but also non-muslim to increase their level of understanding and awareness toward Halal terms.